Hawa` Dalam Perspektif Al-Qur'an (Studi Pendekatan Tafsir Maudhu`iy) - Muhammad Ilham Shaleh (Jurnal Adabiyah: Humanities and Islamic Studies, 2013)
This writing explrores the term hawa and its meaning in al-Quran. This term is found as many as 36 times in various meanings and functions.It sometimes means a desire refering to kindness, sometimes to badness, empity and so forth.  Generally ulama interprites hawa as the inclination to love worldly life. Human being who is always busy with wordly life and ignores even forgets God has regarded hawa as his God. Such this human being will be funished by God not only in hereafter, also in his life in the world.